Parent Support Relationship with Smoking Behavior - Andrianto, Muhammad Bagus; Nirbito, Mochamad Anom; Padila, Padila; Andri, Juli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between parental support and school children's smoking behavior. This research method uses descriptive correlational research with a cross-sectional approach. The study's results based on class and age showed that 22 students, with a percentage of 73.3%, had supportive parental social support, and 16 students, with a rate of 53.3%, had terrible smoking behavior. The P value of parents' social support with smoking behavior is 0.207. In conclusion, it shows no relationship between parental consent and school children's smoking behavior. Keywords: Parents' Social Support, Smoking Behavior, Elementary School Students